Langkah-langkah Dasar dalam Penelitian Ilmiah - An-Nur, Mohammad Haiqal; Fauzi, Abi; Sa’diyah, Rika (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2025)
Scientific research is the main pillar in the development of science, education, and technology, as it serves as a systematic means to test, develop, and validate existing theories. However, many students and novice academics still lack a systematic understanding of the steps involved in scientific research, which negatively affects the quality of scholarly work and reduces publication productivity. This study aims to describe and analyze the basic steps in scientific research and emphasize their urgency in improving research quality in higher education institutions. The method used is qualitative research with a library research approach, involving a review of literature from research methodology books, national and international journal articles indexed by Sinta and Scopus, as well as relevant academic documents. The findings show that the success of scientific research is determined by the coherence between each stage of the research process, starting from problem formulation, systematic literature review, to valid data analysis and interpretation. Comprehensive methodological understanding has been proven to enhance the validity, reliability, and relevance of research findings. Moreover, the application of practical methodology learning, continuous research mentoring, and interdisciplinary collaboration has proven effective in strengthening a culture of research integrity. Thus, mastering the basic steps of scientific research is a prerequisite for improving the quality of research and academic reputation within higher education institutions.